Novel high-purity brightening scratch-free polishing powder and preparation method thereof
High-purity, brightening, and scratch-free alumina polishing powder was prepared through processes such as wet ball milling, surface modification, and low-temperature heat treatment. This solved the problems of low purity, easy scratching, and poor dispersibility in existing technologies, achieving high-efficiency polishing performance and chemical stability, and is suitable for optical glass, semiconductors, and precision devices.
Patent Information
- Application Number
- CN202510871265.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2025-10-31
AI Technical Summary
Existing alumina polishing powders suffer from low purity, easy scratching, poor dispersibility, and insufficient chemical stability in the fields of optical glass and semiconductors, making it difficult to meet the requirements of high-precision polishing.
A high-purity, brightening, scratch-free alumina polishing powder was prepared by combining wet ball milling, surface modification, classification, and low-temperature heat treatment. This process optimized the particle size distribution, improved the powder surface properties, and enhanced dispersibility and chemical stability.
It achieves high-purity, scratch-free polishing results, significantly improves the dispersibility and chemical stability of polishing powder, and is suitable for acidic or alkaline environments. It is suitable for efficient polishing of optical glass, semiconductors and precision devices.
Smart Images

Figure CN120865800A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of materials science and surface treatment technology, specifically to a novel high-purity brightening and scratch-free polishing powder and its preparation method. Background Technology
[0002] Alumina polishing powder, due to its high hardness, chemical stability, and excellent polishing performance, has been widely used in the efficient polishing of optical glass, semiconductors, and precision devices. These fields have extremely stringent requirements for material surface quality, especially in high-end applications such as the manufacture of optical lenses, semiconductor wafers, and precision instruments, which place higher demands on the purity, particle size distribution, morphological characteristics, and polishing effect of the polishing powder. However, existing alumina polishing powders still have many shortcomings in practical applications and cannot fully meet the needs of high-precision polishing.
[0003] First, existing alumina polishing powders generally have low purity and high impurity content. This not only affects the surface finish after polishing but may also introduce additional contamination during the polishing process, thereby reducing product reliability and performance. Especially in the fields of optical glass and semiconductors, even trace amounts of impurities can lead to a significant decline in product performance. Therefore, the market demand for high-purity alumina polishing powder is becoming increasingly urgent.
[0004] Secondly, the problem of scratches easily generated during the polishing process of existing alumina polishing powders has not been effectively solved. This phenomenon is mainly related to the irregular morphology of the powder, uneven particle size distribution, and agglomeration effect between particles. The presence of scratches not only affects the aesthetics of the polished surface, but may also cause irreversible damage to the function of the device. For example, in the polishing of optical glass, scratches will significantly reduce light transmittance; while in semiconductor processing, scratches may cause short circuits or unstable performance.
[0005] Furthermore, existing alumina polishing powders have poor dispersibility and are prone to agglomeration in polishing slurries, thus affecting the uniformity and efficiency of polishing. This problem is particularly prominent in large-scale production, as poor dispersibility leads to increased slurry consumption and prolonged polishing time, thereby increasing production costs. In addition, some polishing powders exhibit poor chemical stability in acidic or alkaline environments, limiting their application under specific process conditions.
[0006] To address the aforementioned issues, while some improved alumina polishing powders have emerged on the market, they often only improve certain specific indicators and cannot comprehensively solve problems such as low purity, susceptibility to scratches, and poor dispersibility. For example, although some high-purity alumina polishing powders can reduce impurity content, their particle size distribution and morphology control are still not ideal, resulting in uneven polishing effects. Other products that improve dispersibility through surface modification may have drawbacks such as complex heat treatment processes and high costs. Summary of the Invention
[0007] To address the significant technical bottlenecks in the purity, polishing effect, dispersibility, and chemical stability of existing alumina polishing powders, which make it difficult to meet the high-precision polishing requirements of modern industry, this invention aims to develop a high-purity, brightening, scratch-free polishing powder and its preparation method. By optimizing the material composition and preparation process, its overall performance is comprehensively improved to meet the urgent needs of the optical glass, semiconductor, and precision device industries for high-efficiency polishing materials.
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] A method for preparing a novel high-purity, brightening, scratch-free alumina polishing powder includes the following steps:
[0010] Step 1: Mix high-purity alumina raw materials with dispersant and then perform wet ball milling, controlling the ball milling time and speed to optimize particle size distribution;
[0011] Step 2: Add the ball-milled powder to the surface modifier solution and stir at a certain temperature to react, so that the modifier is evenly coated on the powder surface;
[0012] Step 3: The modified powder is graded to screen out powders within the target particle size range;
[0013] Step 4: The graded powder is subjected to low-temperature heat treatment to further improve its chemical stability and polishing performance;
[0014] Step 5: Pack the powder in a moisture-proof manner to obtain the finished polishing powder.
[0015] This invention effectively reduces powder agglomeration and improves its surface properties through wet ball milling and surface modification, resulting in excellent brightening and scratch-free performance during polishing. Furthermore, the low-temperature heat treatment process further enhances the chemical stability of the powder, enabling it to maintain stable polishing performance even in acidic or alkaline environments.
[0016] Specifically, in step 1, the wet ball milling time is 8 to 12 hours and the rotation speed is 200 to 400 rpm, preferably 10 hours and the rotation speed is 300 rpm;
[0017] In step 2, the surface modifier is at least one of silane coupling agent, titanate coupling agent or stearic acid, and the amount added is 0.1% to 0.5% of the powder mass, preferably 0.3%.
[0018] In step 2, the temperature of the stirring reaction is 50-80℃, preferably 60℃, and the reaction time is 2-4 hours.
[0019] In step 3, the grading process adopts airflow grading or centrifugal grading, with a target particle size range of 0.5 to 2.0 μm.
[0020] In step 4, the temperature of the low-temperature heat treatment is 800-1200℃, preferably 1000℃, and the holding time is 1-3 hours.
[0021] In step 5, moisture-proof packaging typically uses double-sealed bags with a desiccant placed inside to further reduce humidity.
[0022] The following are relevant embodiments and comparative examples:
[0023] Example 1:
[0024] Raw material: High-purity alumina (Al2O3 content ≥ 99.99%).
[0025] Ball milling time: 10 hours, speed: 300 rpm.
[0026] Surface modifier: silane coupling agent, added at a rate of 0.3%.
[0027] Heat treatment temperature: 1000℃, holding time: 2 hours.
[0028] Classification: Airflow classification is used, with a target particle size of 0.5–1.0 μm.
[0029] Example 2:
[0030] Raw material: High-purity alumina (Al2O3 content ≥ 99.98%).
[0031] Ball milling time: 12 hours, speed: 350 rpm.
[0032] Surface modifier: titanate coupling agent, added at a rate of 0.5%.
[0033] Heat treatment temperature: 1100℃, holding time: 3 hours.
[0034] Grading: Centrifugation was used for grading, with a target particle size of 1.0–2.0 μm.
[0035] Comparative Example 1:
[0036] Raw material: Ordinary alumina (Al2O3 content ≥99.0%).
[0037] No surface modification treatment was performed.
[0038] Heat treatment temperature: 900℃, holding time: 1 hour.
[0039] Classification: Airflow classification is used, with a target particle size of 1.0–2.0 μm.
[0040] Comparative Example 2:
[0041] Raw material: High-purity alumina (Al2O3 content ≥ 99.99%).
[0042] No low-temperature heat treatment was performed.
[0043] Classification: Airflow classification is used, with a target particle size of 0.5–1.0 μm.
[0044] The product performance comparison table is as follows:
[0045] index Example 1 Example 2 Comparative Example 1 Comparative Example 2 Test methods Alumina content (%) ≥99.99 ≥99.98 ≥99.0 ≥99.99 X-ray fluorescence spectroscopy analysis Particle size distribution (μm) 0.5-1.0 1.0-2.0 1.0-2.0 0.5-1.0 Laser particle size analyzer Surface gloss (GU) ≥90 ≥85 ≤70 ≤80 Gloss meter Scratch rate (%) ≤0.1 ≤0.2 ≥1.0 ≥0.5 Microscopic observation and statistics <![CDATA[Specific surface area (m 2 / g)]]> 5.0-6.0 4.0-5.0 3.0-4.0 4.5-5.5 BET method <![CDATA[Bulk density (g / cm 3 )]]> 0.8-1.0 0.9-1.1 0.6-0.8 0.7-0.9 Tap density tester pH value 6.5-7.5 6.0-7.0 5.0-6.0 6.0-7.0 pH meter Moisture content (%) ≤0.1 ≤0.2 ≤0.5 ≤0.3 Karl Fischer
[0046] Furthermore, the present invention also provides a novel high-purity brightening and scratch-free alumina polishing powder, wherein the polishing powder is prepared by the preparation method described in the present invention.
[0047] Specifically, the polishing powder has an alumina content of not less than 99.98%, a particle size distribution of 0.5 to 2.0 μm, a scratch rate of not more than 0.2%, a surface gloss of not less than 85 GU, a specific surface area of 4.0 to 6.0 m2 / g, a bulk density of 0.8 to 1.1 g / cm2, a pH value of 6.0 to 7.5, and a moisture content of not more than 0.2%.
[0048] The polishing powder is used for high-efficiency polishing applications of optical glass, semiconductors, and precision devices.
[0049] Compared with the prior art, the beneficial effects of the present invention are:
[0050] (1) This invention significantly reduces the agglomeration of alumina powder by wet ball milling and surface modification treatment, optimizes the particle size distribution and morphology of the powder, and thus achieves a scratch-free polishing effect.
[0051] (2) The introduction of surface modifiers effectively improves the dispersibility and chemical stability of powder, enabling it to maintain excellent polishing performance in acidic or alkaline environments.
[0052] (3) The mechanical strength and chemical stability of the powder are further enhanced by low temperature heat treatment process, thereby extending the service life of the polishing powder;
[0053] (4) The preparation method provided by the present invention is simple, low-cost, easy to scale up, and can be widely used in the field of high-efficiency polishing of optical glass, semiconductors and precision devices. Attached Figure Description
[0054] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof.
[0055] In the attached diagram:
[0056] Figure 1 This is a flowchart illustrating the steps involved in preparing a novel high-purity brightening and scratch-free polishing powder. Detailed Implementation
[0057] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0059] Please refer to Figure 1 This invention provides a novel high-purity, brightening, scratch-free alumina polishing powder and its preparation method. This method significantly improves the purity, dispersibility, chemical stability, and polishing performance of the alumina polishing powder through the synergistic effect of key steps such as wet ball milling, surface modification, grading, and low-temperature heat treatment. The technical solution, operating principle, and process of this invention are described in detail below with reference to specific embodiments.
[0060] In implementing this invention, high-purity alumina raw materials are first required, with an alumina content of 99.98% or higher to ensure the high purity of the final product. To further optimize the particle size distribution and morphology of the powder, the high-purity alumina raw materials are mixed with an appropriate amount of dispersant and then subjected to wet ball milling. Wet ball milling is one of the key steps in this invention, its purpose being to refine and uniformly disperse the alumina particles through mechanical force, thereby reducing powder agglomeration. According to experimental verification, the preferred wet ball milling time is 8 to 12 hours, and the rotation speed range is 200 to 400 rpm. For example, in Example 1, a ball milling time of 10 hours and a rotation speed of 300 rpm can effectively achieve optimized particle size distribution and obtain ideal specific surface area and bulk density (see product performance comparison table). In addition, the selection of dispersant also has an important impact on the ball milling effect. Commonly used dispersants include ammonium polyacrylate and polyvinyl alcohol, and their addition amount is usually 0.5% to 1.0% of the powder mass.
[0061] After wet ball milling, the alumina powder undergoes further surface modification. Surface modification is one of the core technologies of this invention, aiming to improve the dispersibility and surface properties of the powder by introducing specific surface modifiers, thereby enhancing its brightening effect and scratch-free performance during polishing. In Example 1, a silane coupling agent is selected as the surface modifier, with an addition amount of 0.3% of the powder mass. The specific modification process includes adding the ball-milled powder to a solution containing the surface modifier and stirring the mixture at a temperature range of 50 to 80°C for 2 to 4 hours. Under preferred conditions, the stirring temperature is 60°C, and the reaction time is 3 hours. During this process, the surface modifier molecules uniformly coat the surface of the alumina powder through chemical bonding, forming a stable modified layer. This modified layer not only effectively prevents the re-agglomeration of powder particles but also significantly enhances the chemical stability of the powder in acidic or alkaline environments. In Example 2, a titanate coupling agent was selected as a surface modifier, and its addition amount was 0.5% of the powder mass, which could also improve the dispersibility and chemical stability of the powder to a certain extent.
[0062] After surface modification, the modified powder needs to be graded to screen out powders within the target particle size range. Grading is a crucial step in ensuring uniform particle size distribution of the polishing powder, and the methods include airflow classification and centrifugal classification. In Example 1, airflow classification was used to control the powder particle size within the range of 0.5 to 1.0 μm, a range suitable for efficient polishing of optical glass. In Example 2, centrifugal classification was used to control the powder particle size within the range of 1.0 to 2.0 μm, suitable for polishing semiconductors and precision devices. The effectiveness of the grading process directly affects the polishing performance of the final polishing powder; therefore, grading parameters must be strictly controlled to ensure that the proportion of powder within the target particle size range reaches over 95%.
[0063] The graded powder requires low-temperature heat treatment, which is another key technical aspect of this invention. The main purpose of low-temperature heat treatment is to further improve the chemical stability and mechanical strength of the powder, while eliminating residual stress that may be generated during surface modification. In Example 1, the low-temperature heat treatment temperature was set at 1000℃, and the holding time was 2 hours; while in Example 2, the heat treatment temperature was increased to 1100℃, and the holding time was extended to 3 hours. Experimental results show that low-temperature heat treatment can significantly enhance the polishing performance and service life of the powder.
[0064] After low-temperature heat treatment, the powder needs to be packaged in a moisture-proof manner to prevent it from absorbing moisture during storage and transportation, which would affect its performance. Moisture-proof packaging typically uses double-sealed bags with a desiccant placed inside to further reduce humidity. In actual production, different packaging formats can be customized according to customer needs, such as small bags, drums, or boxes.
[0065] The novel high-purity, brightening, scratch-free alumina polishing powder provided by this invention exhibits excellent performance in practical applications. For example, in the polishing process of optical glass, the polishing powder of Example 1 can significantly improve the gloss of the glass surface, achieving a gloss level of over 90 GU, while maintaining an extremely low scratch rate (≤0.1%). In the polishing application of semiconductor wafers, the polishing powder of Example 2 demonstrates good chemical stability and high polishing efficiency, achieving a surface gloss level of over 85 GU, with a scratch rate controlled below 0.2%. These excellent performance indicators fully demonstrate the practicality and superiority of the technical solution of this invention.
[0066] To further verify the technical effects of the present invention, several comparative experiments were conducted. In Comparative Example 1, using ordinary alumina raw materials without surface modification treatment, the alumina content of its polishing powder was only 99.0%, with a wide particle size distribution, low surface gloss (≤70 GU), and a scratch rate exceeding 1.0%. In Comparative Example 2, although high-purity alumina raw materials were used, the lack of low-temperature heat treatment resulted in significantly insufficient chemical stability and mechanical strength of its polishing powder, with a surface gloss of only around 80 GU and a relatively high scratch rate (≥0.5%). The results of these comparative experiments further highlight the unique advantages of the technical solution of the present invention.
[0067] In summary, this invention successfully prepared a novel high-purity, brightening, scratch-free alumina polishing powder through the synergistic effect of key steps such as wet ball milling, surface modification, grading, and low-temperature heat treatment. This polishing powder not only possesses high purity, uniform particle size distribution, and excellent surface properties, but also maintains stable polishing performance in acidic or alkaline environments, making it widely applicable in the efficient polishing of optical glass, semiconductors, and precision devices. The preparation method of this invention is simple, low-cost, and easily scalable, possessing significant industrial application value.
[0068] The above description is a detailed description of the preferred embodiments of the present invention. However, the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modifications made under the technical spirit of the present invention should fall within the patent scope covered by the present invention.
Claims
1. A method for preparing a novel high-purity, brightening, scratch-free alumina polishing powder, characterized in that, The preparation method includes the following steps; Step 1: Mix high-purity alumina raw materials with dispersant and then perform wet ball milling, controlling the ball milling time and speed to optimize particle size distribution; Step 2: Add the ball-milled powder to the surface modifier solution and stir to react, so that the modifier is evenly coated on the powder surface; Step 3: Classify the modified powder and screen out powders within the target particle size range; Step 4: The graded powder is subjected to low-temperature heat treatment to improve its chemical stability and polishing performance; Step 5: Finally, the powder is packaged in a moisture-proof manner to obtain the finished polishing powder.
2. The preparation method of the novel high-purity brightening and scratch-free alumina polishing powder according to claim 1, characterized in that, The wet ball milling time is 8 to 12 hours, and the rotation speed is 200 to 400 rpm.
3. The preparation method of the novel high-purity brightening and scratch-free alumina polishing powder according to claim 1, characterized in that, The surface modifier is at least one of silane coupling agent, titanate coupling agent or stearic acid, and the amount added is 0.1% to 0.5% of the powder mass.
4. The preparation method of the novel high-purity brightening and scratch-free alumina polishing powder according to claim 1, characterized in that, The temperature of the stirring reaction is 50 to 80°C, and the reaction time is 2 to 4 hours.
5. The preparation method of the novel high-purity brightening and scratch-free alumina polishing powder according to claim 1, characterized in that, The grading process employs airflow grading or centrifugal grading, with a target particle size range of 0.5 to 2.0 μm.
6. The preparation method of the novel high-purity brightening and scratch-free alumina polishing powder according to claim 1, characterized in that, The low-temperature heat treatment is performed at a temperature of 800 to 1200°C for 1 to 3 hours.
7. The preparation method of the novel high-purity brightening and scratch-free alumina polishing powder according to claim 1, characterized in that, The high-purity alumina raw material has an alumina content of not less than 99.98%, and the dispersant is either ammonium polyacrylate or polyvinyl alcohol, with an addition amount of 0.5% to 1.0% of the powder mass.
8. A novel high-purity, brightening, scratch-free alumina polishing powder, characterized in that, The polishing powder is prepared by any one of the preparation methods described in claims 1 to 7; the polishing powder has an alumina content of not less than 99.98%, a particle size distribution of 0.5 to 2.0 μm, a scratch rate of not more than 0.2%, and a surface gloss of not less than 85 GU.
9. The novel high-purity brightening and scratch-free alumina polishing powder according to claim 8, characterized in that, The polishing powder has a specific surface area of 4.0 to 6.0 m² / g, a bulk density of 0.8 to 1.1 g / cm², a pH value of 6.0 to 7.5, and a moisture content of no more than 0.2%.
10. The novel high-purity brightening and scratch-free alumina polishing powder according to claim 9, characterized in that, The polishing powder is used for high-efficiency polishing applications of optical glass, semiconductors, and precision devices.